The Effects of Café Atmosphere, Social Media Marketing, And Electronic Word of Mouth on The Purchase Decision at Nakoa Café - Muhsyi, Ufairoh Aqilah; Ananto Basuki (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The urgency of this research stems from the increasing need for cafés to understand the combined impact of atmosphere, social media marketing, and e-WOM on consumer purchasing decisions in a highly competitive industry. This research is motivated by the growing importance of understanding the factors that influence consumer purchasing decisions in the digital era, particularly in the culinary sector like cafés. As competition in the industry intensifies, the effective use of café atmosphere, social media marketing, and electronic word of mouth (e-WOM) has become crucial. The objective of this research is to identify the effects of café atmosphere, social media marketing, and e-WOM on the decision to purchase products at Nakoa Café. This study adopts a quantitative explanatory research approach. The population consists of student customers of Nakoa Café in Malang city. Using a non-probability sampling method and purposive sampling technique, 200 respondents were selected. Data analysis was conducted using multiple linear regression in IBM SPSS version 26. The results indicate that café atmosphere, social media marketing, and e-WOM have a positive and significant impact on purchase decisions at Nakoa Café. This research provides new insights into the strategic role of these factors in influencing consumer decisions within the café industry and can serve as a reference for future marketing strategies in the sector.